'A military ERP'? Military assistance and US public diplomacy in Norway in the early 1950s. (2nd October 2017) - Danielsen, Helge
Abstract : This article explores how U.S. public diplomacy resources in Norway were mobilised in support of the Mutual Defense Assistance Program in the early 1950s. These efforts had two main objectives: to display U.S. commitment to allied security, and thus provide 'psychological reassurance', and, secondly, to mobilise popular support for increased defence spending by the Norwegian Government. The first ambition played well with local audiences. The second was more controversial, as it could be apprehended as meddling in domestic affairs. Close cooperation with local actors, a characteristic of U.S. public diplomacy in Norway at large, was therefore particularly important in this case.